The reality of inclusive government school principals exercising their supervisory role on the inclusive education program in the capital, Amman from their own point of view - Alqabali, Yahya Ahmad; Mahasees, Samy Sulyman (Journal of Educational and Psychological Sciences, 2023)
Purpose: the aim of the study is to explore the inclusive primary school’s principals’ practices upon supervising the inclusive education program in their schools having into consideration a number of variables such as: gender, seniority level, educational level, inclusive education attended courses& workshops.Method: the sample was 14 inclusive education principals who were intentionally selected from all-inclusive schools in Amman that are sponsored by the American non-governmental organization (Mercy corps- inclusive education program).The descriptive approach was adapted, questionnaire was used to collect the principals’ responses, and each consisted of 50 phrases and 5 dimensions Built and developed based on their expertise, that were answered by the principals of the targeted schools The statistical analysis took place was by the use of; averages, percentages, standard deviations, simple regression and multiple regression.Results: The results show no statistical differences (α ≤ 0.05) on the controlled variables (gender, seniority level and inclusive education courses& workshops).Recommendations: the researchers recommended that the school principals should receive intensive courses in the field of children with disabilities’ inclusive education. The qualitative results also reached several proposals that contribute to improving principals' supervision of inclusive schools.
Keywords: inclusive education; multidisciplinary team